THE RADIAL MOTIONS OF CHARGED PARTICLES IN THE FIELD OF THE CHARGED OBJECT IN GENERAL RELATIVITY AND THEIR CLASSIFICATION - Gladush, V. D.; Galadgyi, M. V. (Одеські астрономічні публікації, 2007)
The radial motions of the charged test particles in the field of a spherically symmetric charged object in general relativity are considered and their classification is built. The conditions of equilibrium for these particles are studied and equilibrium stability conditions are received. It is shown, that stable states are only possible for the bound states of the weakly charged particle in the field of the abnormally charged central source.